EDUKASI PRILAKU CUCI TANGAN PAKAI SABUN DENGAN AIR MENGALIR PADA SEKOLAH DASAR INPRES DI KELURAHAN PARDOMUAN - aspipa, Aspipa permata bunda; Nurlaila (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2024)
Pardomuan Village is located in South Angkola District, South Tapanuli Regency. This service program aims to improve clean and healthy living behavior. Clean and Healthy Living Behavior (PHBS) in the school environment is a set of behaviors that are practiced by students, teachers and the school community as a result of learning problems that arise in elementary schools showing that students do not practice Clean and Healthy Living Behavior (PHBS) such as rarely wash their hands with running water and soap, rarely use healthy latrines, rarely throw rubbish in the right place, resulting in several cases of diseases such as diarrhea, worms, typhoid, ulcers. The method used is to provide direct education and practice directly to elementary school students in the Pardomuan Garonggang sub-district. The results of the observations and counseling that have been carried out can increase knowledge and healthy living behavior.